Como trabalhar a educação florestal na educação infantil: proposta de material didático - Barreto, Francisco Rodolfo da Silva (Universidade Federal Rural do Semi-Árido, 2017)
The use of environmental education has been contradictory in regards to its integration into the basic curriculum, thus it has been worked in one-off, fragmented and without considerable community participation. Forest education emerges as a driving mechanism for environmental education, aiming to provide the individual's direct interaction with forest, promoting the development of ecological awareness towards the use and conservation of forest patrimony. The present work aimed to elaborate a proposal of didactic material for forest education, to be used with children of early childhood education (4 and 5 years) as a learning tool about the importance of the forest in terms of environmental, economic and social benefits. With the help of municipal educators, questionnaires were carried out with teachers of pre-school education in the municipality of Jaguaruna-CE. Information was collected on the use of forest education at the municipal level, then a didactic material composed of a book illustrated in felt and a guide of use intended for the teacher were created and evaluated. In response to the questionnaires, it was observed there was a lack of knowledge of the term forest education by more than 70% of teachers, but in contrast, more than 50% had already used forest themes in the process of learning children. The totality of the teachers emphasized the importance of the use of didactic materials and that would use one that approached forest education. In the elaboration of the didactic material, the following topics were addressed: forest engineer presentation, problems of forest degradation, reforestation as a possible solution, forestry, environmental goods and services of trees and forest products, timber and non-timber products present on daily routines, all of which showed by scenes depicted on felt having different textures to the touch. The users' guide was created to suggest and give additional information to teachers, in a way to improve the material utilization. Attending the teachers demand, a list of activities was included to complement the material. The material was applied in EI IV and V classes of the evaluated age group. There was a direct interaction of the children of both ages with the material, besides the use of suggested activities by all the teachers that tested the material. Teachers positively evaluated the use and quality of the material. Forest issues are used in early childhood education, but the term forest education remains unknown, so the development of didactic material for forest education is an important tool for the popularization of the term and the insertion of a critical training regarding the conservation and sustainable use of forest patrimony, besides presenting the professional forest engineer and its importance.
Monografia
Keywords: Educação florestal; Material didático; Educação infantil; Educação ambiental; Forest education; Educational material; Early childhood education; Environmental education; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL